Disaster Mitigation Information in Football Matches: Fans Perspective - Fajar Junaedi; Filosa Gita Sukmono (Ikatan Sarjana Komunikasi Indonesia, 2019)
The study focuses on problems of disaster mitigation information in football matches and the implications to audiences’ safety. The study uses study case method. The data collection is performed using in-depth interview, observation, and literature review; and the informant selection applies purposive sampling or criterion-based selection. Informants picked are fans of PSIM Yogyakarta, Persiba Bantul, and Persebaya Surabaya who experienced disasters in the stadiums. The study demonstrates, based on fans experiences, that various factors are responsible for outbreaks in football matches, namely the absence of information on disaster mitigation, the unprofessionalism of the organizers and securities in managing possible disasters, the insufficiency of the stadium architecture to deal with disasters, and the inadequacy of medical facilities in emergencies. The way forwards which are proposed is that, firstly, stadium construction should be designed by heeding disaster mitigation consideration for the sake of individuals’ well-being in the stadium. Moreover, the organizers, including the securities, should be more professional in running the matches. Finally, appropriate facilities for preventing disasters should be provided.